Integration of Hepatitis C Treatment in a Primary care Federally Qualified Health Center; Philadelphia, Pennsylvania, 2015-2017. (April 2019) - Bartholomew, Tyler S; Grosgebauer, Kaitlin; Huynh, Katherine; Cos, Travis
Hepatitis C virus (HCV) infection remains a pressing public health issue. Identification of long term infection in primary care settings and community health centers can facilitate patients' access to appropriate care. Given the increase in HCV prevalence in the United States, improving the HCV care continuum and expanding medication access to disproportionately affected populations can help reduce disease burden, health care system costs, and transmission. Innovative treatment programs developed in the primary care setting are needed to deliver quality care to meet the demand of those engaging in treatment. This article describes an HCV treatment program developed within a primary care federally qualified health center (FQHC) using physician assistants (PAs) and nurse practitioners (NPs) to address the high number of HCV positive patients identified at the clinic. An interdisciplinary care team was established to optimize patient experience around HCV care and treatment, using on-site primary care behavioral health consultants, an HCV treatment coordinator, and a 340B contracted specialty pharmacy. From January 2015 to April 2017, the Public Health Management Corporation (PHMC) Care Clinic medical providers referred 189 patients for HCV treatment. Of those referred, 102 patients successfully obtained a sustained virologic response (SVR), representing a 53.7% success rate from referral to cure. This treatment program successfully integrated HCV treatment in a patient population heavily affected by substance use and mental illness. Support and adoption of similar programs in primary care community health centers testing for HCV can help meet the clinical/behavioral needs of these marginalized populations.